2017
DOI: 10.1021/acs.inorgchem.6b02399
|View full text |Cite
|
Sign up to set email alerts
|

Ti(IV) and the Siderophore Desferrioxamine B: A Tight Complex Has Biological and Environmental Implications

Abstract: The siderophore desferrioxamine B (DFOB) binds Ti­(IV) tightly and precludes its hydrolytic precipitation under biologically and environmentally relevant conditions. This interaction of DFOB with Ti­(IV) is investigated by using spectro-potentiometric and spectro-photometric titrations, mass spectrometry, isothermal titration calorimetry (ITC), and computational modeling. The data from pH 2–10 suggest two one-proton equilibria among three species, with one species predominating below pH 3.5, a second from pH 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 61 publications
0
18
1
Order By: Relevance
“…The Ti(IV) deferasirox and BHPT complexes are also more stable than Tshuva et al’s recently produced Ti(IV) complexes of N , N ′-phenolate-substituted HBED derivative ligands, which after a few days in solution begin to exhibit hydrolytic behavior. 51 Ti(IV) complexes of the siderophores enterobactin 52 and desferrioxamine B, 53 iron chelators used by bacteria to scavenge iron, exhibit very high formation constants but have not been reported to display antiproliferative properties presumably because the Ti(IV) is too tightly held. Deferasirox and BHPT highly stabilize Ti(IV) in aqueous solution under physiologically relevant conditions for an indefinite period of time but can be induced to release the metal.…”
Section: Resultsmentioning
confidence: 99%
“…The Ti(IV) deferasirox and BHPT complexes are also more stable than Tshuva et al’s recently produced Ti(IV) complexes of N , N ′-phenolate-substituted HBED derivative ligands, which after a few days in solution begin to exhibit hydrolytic behavior. 51 Ti(IV) complexes of the siderophores enterobactin 52 and desferrioxamine B, 53 iron chelators used by bacteria to scavenge iron, exhibit very high formation constants but have not been reported to display antiproliferative properties presumably because the Ti(IV) is too tightly held. Deferasirox and BHPT highly stabilize Ti(IV) in aqueous solution under physiologically relevant conditions for an indefinite period of time but can be induced to release the metal.…”
Section: Resultsmentioning
confidence: 99%
“…5), suggesting that induction of this cytokine is more sensitive to DEP-associated components such as PAHs or carbon than it is metals. Chen et al documented induction of TNF-a expression alongside mitochondrial membrane dysfunction and inhibition of phagocytic capacity in RAW 264.7 MDM following comparable exposures to TiO 2 nanoparticles (10 mg ml À1 for 24 h) 28 but despite documenting similar toxicity profiles for our particles and considering that DFO binds tightly with titanium(IV) 49 we did not see reductions in TNF-a secretion upon addition of the chelator for either particle. Similarly, DFO did not impair the significant increases in anti-inflammatory IL-10 secretion that were observed following exposure to BAD or SRM-2975 ( Fig.…”
Section: Inflammatory Responsesmentioning
confidence: 44%
“…This result was consistent with previous studies that showed that DFOB forms more stable complexes with Ti(IV) even in presence of an excess of Fe(III). 37,38 Surprisingly, E3 (NH 3 10%, pH 12.6) still showed poor recovery of DFOB (18.7 ± 5.2%). Therefore, pH-adjustment alone did not suffice to desorb hydroxamate-containing ligands from TiO 2 .…”
Section: Elution Buffer Optimizationmentioning
confidence: 95%